Signification and refutation - Cárdenas Mejía, Luz Gloria (Estudios de Filosofía, 2001)
This study reconstructs the assumptions which Aristotle discusses with an opponent, in order to force him to admit the principles of identity, non contradiction and excluded middle, in so far as, without them, it is not posible the construction of true knowledge about things. This is carried out by mean of arguments against the paradox: “A same thing is a nd is-not". The refutation is possible only through the dissolution of the Iogical basis of the paradox. This study will show that it was compulsory for Aristotle the redress of the dissolved bond between words and things, through the elaboration of a theory of meaning.